2018
DOI: 10.1080/10942912.2017.1414841
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of four bioactive compounds in Korean rice wine (makgeolli) by solvent extraction coupled with gas chromatography-mass spectrometry

Abstract: Makgeolli is a traditional Korean rice wine reported to have anticancer, antiinflammatory, and antioxidant effects. We developed an approach involving solvent extraction coupled with gas chromatography-mass spectrometry to determine four bioactive compounds, farnesol (FOH), squalene (SQ), and newly identified 4-vinyl guaiacol (4-VG) and 2,4-di-tert-butylphenol (DTBP), in makgeolli. The method was validated with the linearity, limit of detection, limit of quantification, intra-and inter-day precision, and accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As reported in previous studies, BHT can be added as a preservative to various packaged foods. , Although DBP is not used as a food additive, it was reported to be a natural antioxidant that is present in some foods. , In addition, BHT and DBP are present in food packaging materials and may be transferred into packaged foods. ,, A recent study reported that BHT and DBP are two major SPAs that are widely detected in PCPs . Thus, it can be expected that the increased use of multiple PCPs will lead to greater human exposure to BHT and DBP via dermal absorption.…”
Section: Resultsmentioning
confidence: 90%
“…As reported in previous studies, BHT can be added as a preservative to various packaged foods. , Although DBP is not used as a food additive, it was reported to be a natural antioxidant that is present in some foods. , In addition, BHT and DBP are present in food packaging materials and may be transferred into packaged foods. ,, A recent study reported that BHT and DBP are two major SPAs that are widely detected in PCPs . Thus, it can be expected that the increased use of multiple PCPs will lead to greater human exposure to BHT and DBP via dermal absorption.…”
Section: Resultsmentioning
confidence: 90%
“…One possible pathway is through consumption of rice wine and sweet potato, in which DBP has been reported as natural product. 33,76,77 However, the contributions to DBP via consumption of the above-mentioned products are not available.…”
Section: Human Exposurementioning
confidence: 99%
“…Thus, BHT exposure may occur when people receive medication via intravenous injection. Finally, DBP has been reported as a natural product in rice wine and sweet potato; , thus, consuming these products may contribute to human exposure to DBP.…”
Section: Human Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…By solvent extraction coupled with gas chromatography mass spectrometry (GC-MS) technique, Lee et al (2018) identified four important bioactive compounds in Makgeolli viz. farnesol, squalene, 4-vinylguaiacol and 2,4-di-tert-butylphenol (For chemical structures, see Figure 8).…”
Section: Park Et Al (2018)mentioning
confidence: 99%